Process control as a source of integrator problems for a differential equations course in bioengineering - Merino, Gabriela Alejandra (2013)
Bioengineering is a multidisciplinary program. With its foundations in basic science, Bioengineering applies different technological principles in order to solve problems in the health area. Mathematics, thanks to its methodological and conceptual insights, is an invaluable tool not only in the education of future bioengineers, but also in their professional activities. However, Mathematics courses represent an obstacle to many engineering students. Enhancing the teaching of Mathematics in this context is a need and a challenge for teachers. In this work, problem-solving activities that were carried out in a Differential Equations course are described. They aimed at fostering both the development of the students learning strategies, and the linking of mathematical concepts and methods to other areas. We focused on the possibility of bridging the gap between Differential Equations and Process Control through integrative problem-solving activities that articulate both perspectives and modes of thought.. © 2003-2012 IEEE.